Key role of microsurgical dissections on cadaveric specimens in neurosurgical training: Setting up a new research anatomical laboratory and defining neuroanatomical milestones - Fava, Arianna; Gorgoglione, Nicola; De Angelis, Michelangelo; Esposito, Vincenzo; di Russo, Paolo (Frontiers in Surgery, 2023)
Neurosurgery is one of the most complex surgical disciplines where psychomotor skills, deep anatomical, and neurological knowledge find their maximum expression. A long preparation is necessary to acquire a solid theoretical background and technical skills, to improve manual dexterity and visuospatial ability, and to try and refine surgical techniques. Moreover, both studying and surgical practice are necessary to understand deeply the neuroanatomy, the relationships between structures, and the 3-dimensional orientation that is the core of neurosurgeons’ preparation. For all these reasons, a microsurgical neuroanatomy laboratory with human cadaveric specimens results in a unique and irreplaceable training tool that allows the reproduction of patients’ positions, 3D anatomy, tissues’ consistencies, and step-by-step surgical procedures almost similar to the real ones. We describe our experience in setting up a new microsurgical neuroanatomy lab (IRCCS Neuromed, Pozzilli, Italy) focusing the attention on the development of training activity programs and microsurgical milestones useful to train the next surgeons’ generation. All the required materials and instruments were listed. Six competency levels were designed according to the year of residency and training exercises/procedures defined for each competency level: 1) soft tissue dissections, bone drilling, and microsurgical suturing, 2) basic craniotomies, neurovascular anatomy, 3) white matter dissection, 4) skull base transcranial approaches, 5) endoscopic approaches, 6) microanastomosis. A checklist with the milestones was provided. Microsurgical dissection of human cadaveric specimens is the optimal way to learn and train on neuroanatomy and neurosurgical procedures before safely performing them in the operative room. We provided a “neurosurgical booklet” with progressive milestones for neurosurgical residents. This step-by-step operative program may improve the quality of operative training and guarantee equal skills acquisition all over the Countries. We believe that more efforts should be done to create new microsurgical laboratories, popularize the importance of body donation, and establish a network between Universities and Laboratories to introduce a compulsory operative training program.